2016
DOI: 10.3329/dujbs.v25i1.28495
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation in relation to depression, loneliness and hopelessness among university students

Abstract: The purpose of the present study was to examine the relationship between suicidal ideation and depression, loneliness, hopelessness among University students. Study sample is comprised of 112 University students (51 males and 61 females) drawn by using purposive sampling technique. Standard questionnaires were used to obtain the data from the participants in a cross-sectional survey. The obtained data were analyzed by using Pearson product moment correlation and stepwise multiple regression. Results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 16 publications
(17 reference statements)
3
18
0
Order By: Relevance
“…Studies also suggested that loneliness linked to anxiety, depression, suicidal ideation, hopelessness, etc. (Cacioppo et al, 2006;Johnson et al, 2001;Pervin & Ferdowshi, 2016;Richardson et al, 2017;Roberts et al, 1998). Figure 1 suggested a mediating role of Facebook timeline browsing in the relationship between loneliness and mental health.…”
Section: Discussionmentioning
confidence: 96%
“…Studies also suggested that loneliness linked to anxiety, depression, suicidal ideation, hopelessness, etc. (Cacioppo et al, 2006;Johnson et al, 2001;Pervin & Ferdowshi, 2016;Richardson et al, 2017;Roberts et al, 1998). Figure 1 suggested a mediating role of Facebook timeline browsing in the relationship between loneliness and mental health.…”
Section: Discussionmentioning
confidence: 96%
“…More closely examining loneliness during the COVID-19 pandemic may offer insight into college students' depression, which has been linked to social and interpersonal variables (Alsubaie et al, 2019;Lee et al, 2014;Wright et al, 2014). Loneliness has been related to college student's current depression (e.g., Ceyhan & Ceyhan, 2011;Doğan et al, 2020;Pervin & Ferdowshi, 2016;Wright et al, 2014) and future depression (Rich & Scovel, 1987;Richardson et al, 2017;Wei et al, 2005). The association between loneliness and depression among college students has also been observed during the COVID-19 pandemic (Elmer et al, 2020;Misirlis et al, 2020;Son et al, 2020).…”
Section: Loneliness and Depression During Covid-19mentioning
confidence: 99%
“…More closely examining loneliness during the COVID-19 pandemic may offer insight into college students' depression, which has been linked to social and interpersonal variables (Alsubaie et al, 2019;Lee et al, 2014;Wright et al, 2014). Loneliness has been related to college student's current depression (e.g., Ceyhan & Ceyhan, 2011;Doğan et al, 2020;Pervin & Ferdowshi, 2016;Wright et al, 2014) and future depression (Rich & Scovel, 1987;Richardson et al, 2017;Wei et al, 2005). When evaluating temporal direction, studies suggest loneliness leads to depression, more so than vice versa, in college students (Rich & Scovel, 1987;Richardson et al, 2017;Vanhalst, Luyckx, Teppers et al, 2012).…”
Section: Loneliness and Depression In College Studentsmentioning
confidence: 99%